COMMUNITY EMPOWERMENT IN THE USE OF HERBAL PLANTS TO IMPROVE THE IMMUNE SYSTEM IN SIMO ANGIN-ANGIN VILLAGE, WONOAYU DISTRICT, SIDOARJO REGENCY - Maat, Suprapto; Nidianti, Ersalina; Kurniasari, Diyan Wahyu; Algristian, Hafid (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Medical plants that have uses or properties in health treatment. Currently, the use of Indonesian herbal plants is only limited to being used as cooking spices and has not been optimally used as medicine to increase the body's endurance. The aim of this community service activity is as an effort to prevent disease by increasing the body's immunity after the Covid-19 pandemic. The method applied in this community service activity is community empowerment in the use of herbal plants to improve the immune system in Simo Angin - Angin village, Wonoayu District through the stages of lectures, demonstrations and collaboration. The target participants were PKK women from Simo Angin-angin Village, Wonoayu District, Sidoarjo Regency, a total of 30 people. The results obtained were counseling and education on the benefits of Indonesian herbal plants using posters and brochures. The results of the community empowerment activities in Simo Angin-angin village are through making herbal plants as drinks in the form of herbal medicine to increase the body's immunity. Participants can understand the potential of herbal plants to be processed into drinks that can be consumed to maintain health after Covid-19. The conclusion is that the PKK women in Simo Angin-angin Village, Wonoayu District, Sidoarjo Regency know how to prevent disease by using Indonesian herbal plants and producing herbal drink concoctions to increase the body's immunity. The next recommendation for community service activities is processing residents' empty land for herbal plants and community empowerment through the production of herbal drinks to commercialization.